PERLINDUNGAN HUKUM BAGI ISTRI DAN ANAK DALAM PERKAWINAN TIDAK DICATAT TERHADAP HAK WARISNYA - Rif’atul Khusnia (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract Forms of protection of children's rights as stipulated by Article 28B (2) and Article 28D paragraph (1) of the 1945 Constitution, it will be maximized if all marriages registered. Potential losses from the marriage that is not based on Law No. 1 In 1974, for the woman (wife) are very diverse, but it is actually the most important thing is whether such losses can be recovered or not. This is where the crucial point of Law No. 1 of 1974 mainly arrangements regarding registration of marriages. In the context of the legal system of marriage, protection of the law by the state (government) against the parties involved in marriage, especially against women as a wife, only be done if the marriage is done consciously in accordance with Law No. 1 of 1974, which is one of the conditions is done by registered marriage in accordance with the legislation in force (vide Article 2 of Law No. 1 of 1974). Further consequences, against marriage conducted without registered, the state can not provide legal protection of the status of marriage, joint property, inheritance and other rights arising from the marriage, because to prove the existence of the right of women (wives) to be proved first the marriage between a woman (wife) with her husband. Writing method in this thesis is normative. The objective is to identify and analyze forms of legal protection for his wife and children according to the marriage law article 2, paragraph (1) of the marriage were not recorded and the right beneficiaries. Key words: system marriage law, legal protection, marriage registration Abstrak Bentuk Perlindungan terhadap hak anak sebagaimana diatur oleh Pasal 28B ayat (2) dan Pasal 28D ayat (1) UUD 1945,justru akan dapat dimaksimalkan apabila semua perkawinan dicatatkan. Potensi kerugian akibat perkawinan yang tidak didasarkan pada UU No. 1 Tahun 1974, bagi wanita (istri) sangat beragam, tetapi sebenarnya yang terpenting adalah apakah kerugian tersebut dapat dipulihkan atau tidak. Di sinilah titik krusial UU No. 1 Tahun 1974 terutama pengaturan mengenai pencatatan perkawinan. Dalam konteks sistem hukum perkawinan, perlindungan hukum oleh negara (Pemerintah) terhadap pihak-pihak yang terkait dalam perkawinan, terutama terhadap wanita sebagai istri, hanya dapat dilakukan jika perkawinan dilakukan secara sadar sesuai dengan UU No. 1 Tahun 1974, yang salah satu syaratnya adalah perkawinan dilakukan dengan dicatatkan sesuai dengan peraturan perundang-undangan yang berlaku (vide Pasal 2 UU No. 1 Tahun 1974). Konsekuensi lebih jauh, terhadap perkawinan yang dilaksanakan tanpa dicatatkan, negara tidak dapat memberikan perlindungan hukum mengenai status perkawinan, harta bersama, waris, dan hak-hak lain yang timbul dari sebuah perkawinan, karena untuk membuktikan adanya hak wanita (istri) harus dibuktikan terlebih dahulu adanya perkawinan antara wanita (istri) dengan suaminya. Metode penulisan dalam tesis ini adalah yuridis normatif. Adapun tujuannya adalah untuk mengetahui dan menganalisa bentuk perlindungan hukum bagi istri dan anak menurut undang-undang perkawinan pasal 2 ayat (1) terhadap perkawinan yang tidak dicatat maupun hak warisnya. Kata kunci: sistem hukum perkawinan, perlindungan hukum, pencatatan perkawinan